Teaching language to grade six deaf children - Bertumen, Leticia Z. 1939- (College of Education, University of the Philippines Diliman, 1969)
The study delved into the problem of how language as a subject may be best taught to deaf children. The method of instruction of the deaf in language according to Davis and Silverman was used. Language learning can be accelerated and much of its success depends on the teacher's ingenuity, diligence, and ever alert mind to be on the look out for possible occasion for her pupils' use of language.